Tooth replacement for partially dentate elders: A willingness-to-pay analysis. (October 2016) - McKenna, G.; Tada, S.; Woods, N.; Hayes, M.; DaMata, C.; Allen, P.F.
Abstract: Objectives: The primary aim of this study was to investigate partially dentate elders' willingness-to-pay (WTP) for two different tooth replacement strategies: Removable Partial Dentures (RPDs) and, functionally orientated treatment according to the principles of the Shortened Dental Arch (SDA). The secondary aim was to measure the same patient groups' WTP for dental implant treatment. Methods: 55 patients who had completed a previous RCT comparing two tooth replacement strategies (RPDs (n = 27) and SDA (n = 28)) were recruited (Trial Registration no. ISRCTN26302774). Patients were asked to indicate their WTP for treatment to replace missing teeth in a number of hypothetical scenarios using the payment card method of contingency evaluation coupled to different costs. Data were collected on patients' social class, income levels and other social circumstances. A Mann-Whitney U Test was used to compare differences in WTP between the two treatment groups. To investigate predictive factors for WTP, multiple linear regression analyses were conducted. Results: The median age for the patient sample was 72.0 years (IQR: 71–75 years). Patients who had been provided with RPDs indicated that their WTP for this treatment strategy was significantly higher (€550; IQR: 500–650) than those patients who had received SDA treatment (€500; IQR: 450–550) (p = 0.003). However patients provided with RPDs indicated that their WTP for SDA treatment (€650; IQR: 600–650) was also significantly higher than those patients who had actually received functionally orientated treatment (€550; IQR: 500–600) (p < 0.001). The results indicated that both current income levels and previous treatment allocation were significantly correlated to WTP for both the RPD and the SDA groups. Patients in both treatment groups exhibited little WTP for dental implant treatment with a median value recorded which was half the market value for this treatment (€1000; IQR: 500–1000). Conclusions: Amongst this patient cohort previous treatment experience had a strong influence on WTP as did current income levels. Both treatment groups indicated a very strong WTP for simpler, functionally orientated care using adhesive fixed prostheses (SDA) over conventional RPDs. Clinical significance: Partially dentate older patients expressed a strong preference for functionally orientated tooth replacement as an alternative to conventional RPDs.